2017
DOI: 10.1016/j.jlp.2016.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Flammability limits, explosion pressures, and applicability of Le Chatelier's rule to binary alkane–nitrous oxide mixtures

Abstract: Lower and upper flammability limits (LFL and UFL) and explosion pressures of binary alkane-N 2 O mixtures are investigated.  Binary alkane-N 2 O mixtures exhibit smaller LFLs than corresponding binary alkane-O 2 mixtures.  For binary alkane-N 2 O mixtures, LFL and UFL can be predicted using the Le Chatelier's formulae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Several studies were conducted in the past to provide information on explosions in fuel-N 2 O mixtures. Some authors [6][7][8][9][10][11][12][13][14][15] reported the explosion parameters such as the flammability limits, the maximum explosion pressures, the explosion times, or the deflagration indices for explosions occurring in closed cells in the presence of N 2 O as oxidizer. The laminar combustion velocity of fuel-N 2 O and fuel-N 2 O-diluent mixtures (fuels: NH 3 , CO, H 2 , C 2 H 4 and C 2 H 2 ) was investigated mainly by burner method [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were conducted in the past to provide information on explosions in fuel-N 2 O mixtures. Some authors [6][7][8][9][10][11][12][13][14][15] reported the explosion parameters such as the flammability limits, the maximum explosion pressures, the explosion times, or the deflagration indices for explosions occurring in closed cells in the presence of N 2 O as oxidizer. The laminar combustion velocity of fuel-N 2 O and fuel-N 2 O-diluent mixtures (fuels: NH 3 , CO, H 2 , C 2 H 4 and C 2 H 2 ) was investigated mainly by burner method [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Estimating the LFL of fuel mixtures, characterized by their mole fractions, follows a similar process to that of pure fuels. 12 Firstly, the total number of moles of carbon and hydrogen in the mixtures and the enthalpy of formation of the mixtures are determined.…”
Section: Theory Of Calculated Flame Temperature (Cft) Modelingmentioning
confidence: 99%
“…The calculated adiabatic flame temperature (CAFT) model was created using the energy balance equation to evaluate the flammability limit by assuming a temperature threshold or estimated adiabatic flame temperature. [7][8][9][10][11][12][13] Liaw et al 14,15 developed a new derivation for this rule based on the idea of the threshold temperature. The crucial assumption required to achieve this mixing rule was that each combustible component's adiabatic flame temperature increase at LFL was equal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the main drawbacks of NOFBX are the high combustion temperatures and the hazards connected to flame flashback and possible explosion or even detonation [6,11]. Due to the mentioned challenges, part of studies [19][20][21][22] has been carried out on fundamental combustion properties due to the frequent accidents. The effect of pressure and mixture composition on auto-ignition boundary temperature was assessed, and the dynamic mechanism was verified by the ignition delay time.…”
Section: Introductionmentioning
confidence: 99%